PENDIDIKAN KONSERVASI SEBAGAI BENTUK BELA NEGARA DI KAWASAN GILI AIR, GILI MENO, DAN GILI TRAWANGAN KABUPATEN LOMBOK UTARA - Martayadi, Uwi; Indraswati, Dyah; Mahsar, Lalu; Supriyadi, Erri; Athar, Lalu Mohammad Iswadi; Widiani, Luh; Ali, Muharis (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
Gili Matra is very famous for its underwater natural beauty in the form of coral reefs, seagrasses, reef fish, mangroves, turtles and others. However, this beauty is threatened by various irresponsible human activities that cause environmental damage. Environmental damage occurs due to the increase in the number of tourists in Gili Matra. The increase in the number of tourists is causing serious damage, such as damaged coral reefs and plastic waste piling up. Community Service (PKM) uses the lecture and question and answer method. The results of this PKM are: 1) Lecturers and students of STP Mataram realize the importance of conservation education which is part of efforts to defend the country and is an important step in maintaining environmental sustainability in the Gili Matra area. 2) The knowledge of STP Mataram students and lecturers about conservation, the impact of human activities on the environment, and marine ecosystems such as coral reefs, seagrass, marine fish and others has increased significantly. In conclusion, conservation education as a form of national defense in Gili Matra requires continuous efforts to increase public understanding so that the natural beauty of this island can continue to be maintained and support sustainable tourism.